UPAYA PENINGKATAN HASIL BELAJAR SISWA PADA MATERI KOMPONEN BIOTIK DENGAN PENERAPAN METODE QUANTUM LEARNING PADA SISWAKELAS VII SMP SWASTA ADVENT 2 PEMATANGSIANTAR TAHUN AJARAN 2014/2015 - Rajagukguk, Salome (Jurnal Metabio, 2022)
This study was conducted to determine efforts to improve student learning outcomes in the biotic component topic through the application of Quantum Learning to seventh-grade students at SMP Swasta Advent 2 Pematangsiantar in the 2014/2015 academic year. The study was conducted from May 19-30, 2015, with a sample size of 16 seventh-grade students. The learning process consisted of cycles I and II, involving teaching and evaluation. Data analysis techniques used included calculating class averages, learning completion levels, and classical regression. Based on the results, it can be concluded that learning outcomes in cycle I were 18.75% below the Minimum Competency (KKM). This was followed by cycle II, where 93.75% achieved the KKM.